The variation and controls of mean transit times in Australian headwater catchments. Issue 21 (3rd August 2020) - Cartwright, Ian; Morgenstern, Uwe; Howcroft, William; Hofmann, Harald; Armit, Robin; Stewart, Michael; Burton, Chad; Irvine, Dylan
Abstract: Determining mean transit times in headwater catchments is critical for understanding catchment functioning and understanding their responses to changes in landuse or climate. Determining whether mean transit times (MTTs) correlate with drainage density, slope angle, area, or land cover permits a better understanding of the controls on water flow through catchments and allows first‐order predictions of MTTs in other catchments to be made. This study assesses whether there are identifiable controls on MTTs determined using 3 H in headwater catchments of southeast Australia. Despite MTTs at baseflow varying from a few years to >100 years, it was difficult to predict MTTs using single or groups of readily‐measured catchment attributes. The lack of readily‐identifiable correlations hampers the prediction of MTTs in adjacent catchments even where these have similar geology, land use, and topography. The long MTTs of the Australian headwater catchments are probably in part due to the catchments having high storage volumes in deeply‐weathered regolith, combined with low recharge rates due to high evapotranspiration. However, the difficulty in estimating storage volumes at the catchment scale hampers the use of this parameter to estimate MTTs. The runoff coefficient (the fraction of rainfall exported via the stream) is probably also controlled by evapotranspiration and recharge rates. Correlations between the runoff coefficient and MTTs in individual catchments allow predictions of MTTs in nearby catchments to be made. MTTs are shorter in high rainfall periods as the catchments wet up and shallow water stores are mobilized. Despite the contribution of younger water, the major ion geochemistry in individual catchments commonly does not correlate with MTTs, probably reflecting heterogeneous reactions and varying degrees of evapotranspiration. Documenting MTTs in catchments with high storage volumes and/or low recharge rates elsewhere is important for understanding MTTs in diverse environments. Abstract : Mean transit times estimated using tritium in Australian headwater catchments at baseflow conditions are years to decades. The long mean transit times result from a deeply‐weathered regolith coupled with high evapotranspiration rates. The large catchment storages buffer the streamflow against the impact of short‐term climate variability.